STRATEGI KOMUNIKASI PERNIKAHAN ANTARBUDAYA GENERASI Z DALAM MEMBINA PERNIKAHAN ANTAR BUDAYA DI KECAMATAN BATU AJI KOTA BATAM - ritonga, nanang eko sptian (Commed Jurnal Komunikasi dan Media, 2025)
This study aims to describe the intercultural communication strategies employed by Generation Z families in maintaining intercultural marriages in Batu Aji District, Batam City. The focus of the study includes the patterns, forms, and communication activities within intercultural couple interactions. This research adopts a qualitative approach using phenomenological methods and is grounded in Gudykunst’s Anxiety/Uncertainty Management (AUM) theory. The findings reveal that dominant forms of communication include verbal and nonverbal communication, as well as open, adaptive, and closed communication styles. Communication activities are reflected in high levels of interaction intensity and mutual openness between partners. These findings indicate that the effectiveness of intercultural communication among Generation Z couples is significantly influenced by their ability to adapt and manage anxiety and uncertainty in cross-cultural interactions.